2023
DOI: 10.1038/s41467-023-35850-4
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry-breaking host–guest assembly in a hydrogen-bonded supramolecular system

Abstract: Bio-inspired self-assembly is invaluable to create well-defined giant structures from small molecular units. Owing to a large entropy loss in the self-assembly process, highly symmetric structures are typically obtained as thermodynamic products while formation of low symmetric assemblies is still challenging. In this study, we report the symmetry-breaking self-assembly of a defined C1-symmetric supramolecular structure from an Oh-symmetric hydrogen-bonded resorcin[4]arene capsule and C2-symmetric cationic bis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…The anion contains sulfur and fluorine, which have a similar charge distribution electronegative property as the hydroxyl group from the organic linker, which can provide strong electrostatic forces. The oxygen from the [TFSI] − anion displays strong intermolecular forces with the hydroxyl part of the organic linker, causing an orientation twist with an intermolecular distance of 1.74784 Å, which corresponds to strong hydrogen bonding [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The anion contains sulfur and fluorine, which have a similar charge distribution electronegative property as the hydroxyl group from the organic linker, which can provide strong electrostatic forces. The oxygen from the [TFSI] − anion displays strong intermolecular forces with the hydroxyl part of the organic linker, causing an orientation twist with an intermolecular distance of 1.74784 Å, which corresponds to strong hydrogen bonding [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…13). 65 The NMR studies proved that all resorcin[4]arene units were fixed in a non-equivalent environment around the Ir III complex guest in the NMR time scale, forming a defined C 1 symmetric host–guest complex (Fig. 13b).…”
Section: Confined Spaces In Resorcin[4]arene Assemblies Directed By H...mentioning
confidence: 90%
“…15b). 65 Interestingly, the X-ray structure showed that the stoichiometry of the inclusion complex was a 3 : 1 host–guest complex, which was far different from the solution state. The trimeric capsule structure was stabilized by multiple hydrogen-bonding networks among the counter anions of the metal complex, solvent molecules, and hydroxy groups in the resorcin[4]arene units.…”
Section: Confined Spaces In Resorcin[4]arene Assemblies Directed By H...mentioning
confidence: 99%
“…Self-assembly has been proved to be a powerful strategy for precisely controlling the arrangement of building blocks and amplifying the g lum . [21][22][23][24][25][26] Chiral nematic liquid crystals (NLCs) as a typical 1D chiral photonic crystals (CPCs) of helical structures have been recognized as powerful platforms to generate CPL. [27] For instance, in our previous work, we achieved tunable CPL with a large |g lum | value up to 0.25 through the coassembly of inorganic nanowires and quantum dots into CPCs via Langmuir-Schaefer technique.…”
Section: Introductionmentioning
confidence: 99%